Rancang Bangun Robot Penghindar Halangan Dengan Metode PID - M. Amirul Ummah F.A.B (Pusat Riset dan Inovasi Nasional, 2023)
The development of increasingly advanced science and technology has produced many innovations in meeting the needs of mankind. One area that is developing comprehensively is robotic technology, one of which is obstacle avoidance robots which is an example of a device used to improve the safety and effectiveness of human work. This study aims to design and develop obstacle avoidance robots using the PID (Proportional, Integral, and Derivative) method and ultrasonic sensors. Robots are designed to automatically detect and avoid obstacles in their environment by using ultrasonic sensors to measure the distance between the robot and existing objects. The PID method is used to control the movement of the robot based on information received from the ultrasonic sensor with Arduino Uno as the main brain controlling the DC motor. Ultrasonic sensors are used to measure the distance between the robot and obstacles in front of it. The distance data obtained from the ultrasonic sensor is then processed using the PID method to produce a control signal that regulates the speed and direction of the robot's movement. The robot is equipped with an obstacle avoidance mechanism that allows it to change its direction of movement automatically when it detects an obstacle in front of it by testing it in various obstacle avoidance scenarios. The results of the tests that have been carried out show that the robot is able to detect different obstacles with high accuracy and avoid them successfully. The use of the PID method in controlling the robot's movement has proven to be effective in maintaining the stability and accuracy of the robot's movement. This research contributes to the development of robotics and automation technology by presenting an obstacle avoidance robot that can move automatically and avoid obstacles effectively.